Analisis Pengaruh Penambahan Senyawa Fire Retardant terhadap Sifat Ketahanan Api, Kekuatan, Keuletan, dan Kekakuan Glass Fiber Reinforced Polymer (GFRP) - Jasillatul Hikmiyah; Wiwik Dwi Pratiwi; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Glass Fiber Reinforced Polymer (GFRP) is one type of material is widely used in manufacturing land transportation components, especially is train. The requirement of material for thetrain must be fire resistance. But in the other hand the GFRP material is still have weakness in high temperature. So, in this case it can provide an opportunity to take experiment about the GFRP material. The experimental method to improvement of GFRP material is adding additive fire retardant as a filler. The additive fire retardant used as a filler is magnesium hydroxide. The method for making specimens of GFRP fire retardant using hand layup method. GFRP which has been added with magnesium hydroxide is tested for fire resistance according to the ORE B 106.2 standart and the tensile strength according to the ASTM D-638 standart. The results show that after adding 30%, 35%, 40%, 45%, and 50% magnesium hydroxide by weight of polyester resin can increase the fire resistance of GFRP. The addition of magnesium hydroxide in the polyester resin caused reducing the tensile strength and modulus of elasticity. Fire resistance, tensile strength, elongation, and modulus of elasticity obtained optimum at the addition 35% magnesium hydroxide by weight of polyester resin. The result show that the carbonized surface of 68,67 cm2, time afterburn was 3,6 second after the flame has been extinguished, tensile strength of 70,86 MPa, elongation of 11,92%, and modulus of elasticity is 5,96 MPa. Therefore, GFRP with the addition 35% of magnesium hydroxide can be fire resistance, but it can't be used as an interior of the train because the tensile strength is less than standart.